When Experts Become Liabilities: Domain Experts on Boards and Organizational Failure - Almandoz, Juan; Tilcsik, András (Academy of Management Journal, 2016)
How does the presence of domain experts on a corporate board—directors whose primary professional experience is within the focal firm’s industry—affect organizational outcomes? We argue that under conditions of significant decision uncertainty, a higher proportion of domain experts on a board may detract from effective decision making and thus increase the probability of organizational failure. Building on exploratory interviews with board members and CEOs, we derive hypotheses from this argument in the context of local banks in the United States. We predict that the greater the level of decision uncertainty—due to rapid asset growth or operation in less predictable markets—the stronger the relationship between the proportion of banking expert directors and the probability of bank failure. Longitudinal analyses of 1,307 banks between 1996 and 2012 support this prediction, even after accounting for both the overall level of professional diversity among directors and banks’ different propensities to have an expert-heavy board. We discuss implications for the key dimensions of board composition, the conditions under which the professional background of directors is more or less consequential, and the mechanisms whereby board composition affects organizational outcomes.